DEVELOPING INTRAPERSONAL INTELLIGENCE THROUGH TECHNIQUE "MAKE-BELIEVE PLAY" IN ORDER TO MAKE CHARACTERIZED EARLY AGE CHILDREN - Kurniah, Nina (Indonesian Journal of Early Childhood Education Studies, 2012)
This study aimstodevelopintrapersonalintelligencein realizingthecharacterized early childhood, throughthe technique of "Make-believeplay" inlearning, meanwhile, the focusof the problem ishow to optimize the intra personal intelligence in learning by using these techniques. This study is aClass Action Research (Classroom ActionResearch), followed By smallexperiments toseethe effectiveness ofactions taken. Subjectswere 24 children aged technique âmake-believe playâ and character 5-6Â  yearsÂ  oldÂ  inÂ  groupÂ  B,Â  inÂ  thekindergartenAl-Muhajirin BengkuluCity.Â  Selected activitiesin developingthe character is the technique of "make-believe play" in the classroom. The research data obtained were processed using a percentage. The analysis showed tha the application of "make-believe play" inlearning, it can develop intra personal intelligence in an effort to make characterized early childhood